A Critical Study on the Political Vision of Vidyaranya: Unveiling the Political Vision of Vidyaranya: An Exploration of Ancient Wisdom for Modern Governance (Journal of Advances and Scholarly Researches in Allied Education, 2016)
Vidyaranya political Thoughts is not alone a mere simple political thought but it is well nurtured with the water of Vedas, Mahakavyas and the experience of the old sages such as Vaalmeeki vishwamitra Agasthiar etc. they are several studies were carried out to trace out the art culture, History and political Vision of Vidyaranya. All these are old and time out of fashions about the entire Political Vision of Vidyaranya during the old age low it can be utilized in the modern age political and administrative circumstances. Present study the life and inner qualities of a king maker, patron royal Priest (Raja guru) sage, eminent comparison and Philosopher, mentor to the royal personalities. The purpose of this brief research work is to introduce Political Vision of Vidyaranya Ideological to the non-political philosophy Scholars.